(3GdGJLGgGJ GdOhdjI GdMOjKI aj efXeGJ GdGYeGd (B:s (3GdJMOjGJ h GdaQU h GdBaGb (B/s ((3YeGf(B: s (3ecJHI GdeLJeY(B, s, 2010)
(3efgL GdcGOQ GdbOhI h OhQg aj GdJfejI GdGLJeGYjI h GdKbGajI GdeSJOGeIaj GdefXeI , OhQ h GgejI GdJLGQI GdGdcJQhfjI h hBaGb JWhQgG aj GdOhd GdYQHjI , GdJLGQI GdGjdcJQhfjI h GTcGdjI LHGjJgG , fXQjI YQHjI aj GdGOGQI ef CLd GdJfejI GdeSJOGeI , eOi JWHjb eYGjjQ GOGQI GdLhOI GdTGedI aj GdHfhc GdYGedI aj adSWjf , JMOjO GMJjGLGJ GdeSJKeQjf ddeYdheGJ , JWHjb GdeUGQa debQQGJ dLfI GdHGRd GdKGfjI GdeJYdbI HGdQbGHI GdOGNdjI , OhQ h CKQ HjGfGJ bGFeI GdJOabGJ GdfbOjI Ydi bQGQGJ GdeSJKeQjf , OhQ dLfI HGRd aj JOhjd bhGYO GOGQI GdHfhc , eOi JWHjb TQcGJ bWGY GdcgQHGA aj GdGQOf dfXGe GdJcGdja h GdGOGQI MSH GdfTGW , GdJMce GdeDSSj h OhQg aj JYRjR GdGJLGgGJ GdOhdjI GdMOjKI aj GdJObjb , eOi JWHjb eYGjjQ GdJWHjb GdOGNdj GdeJYGQa YdjgG aj TQcGJ GdJCejf GdGQOfjI , CgejI JWHjb GdeYjGQ GdeMGSHj GdOhdj (B(32) : (3GdCOhGJ GdeGdjI h GdGaUGM h GdYQV h JCKjQg Ydi YQV GdbhGFe GdeGdjI aj GdHfhc GdJLGdGjI GdGQOfjI , CgejI GdJRGe GdTQcGJ GdeSGgeI GdCQOfjI HJWHjb GdeYGjjQ GdeMGSHjI GdOhdjI aj EYOGO GdJbGQjQ GdeGdjI ef hLgI fXQ eObbj GdMSGHGJ , GSJNOGe WQjbI eYOd SGYI GTZGd GdeGcfI (BMHR (3aj GMJSGH GdJcGdja(B.s
(3eQGLY U(B.559s
Keywords: (3EOGQI GdGYeGds; (3GdJLGQIs; (3efXeGJ GdCYeGds